For an aesthetics of ambiance - Jean-François Augoyard (Ambiances)
Why an aesthetics of ambiances? The answer to this question if far from being solely theoretical. It is associated with my personal career in research and academic teaching since the 1980s.On the one hand, observing everyday ethos, through walks, landscape sensitivity, sound practices, the reception of architecture and street arts have revealed the ambiance as an essential way to question the substance of what is unseen, the nature of the background to the lived environment.On the other hand, throughout my classes and aesthetics seminars in urban planning and architecture, “art’s place” in professions dominated by function forced me to rethink aesthetics as freed from its artistic imperative and digging into its more universal sensitive and atmospheric foundations.This paper reviews an aesthetics of ambiances that is currently being built, working on four levels. At the aesthetic level: what is the imperceptible? What role do non-visible forms play? At the epistemic level: how do we integrate the relevant knowledge that is still too exclusive? At the rhetorical level: how do the components of an ambiance organise themselves, and how can we name the configurations? At the level of aesthetic competence: who makes an ambiance? How are creation and reception divided?